1990
DOI: 10.1016/0014-5793(90)81010-l
|View full text |Cite
|
Sign up to set email alerts
|

Expression of scinderin, an actin filament‐severing protein, in different tissues

Abstract: Scinderin is a calcium-dependent actin filament-severing protein recently discovered in the chromaffin cells of adrenal medulla. In view of the wide tissue distribution of gelsolin, another actin filament-severing protein, experiments were performed to determine the tissue expression of scinderin. Extracts prepared from different bovine tissues were tested by actin-DNase I Sepharose 4B-binding procedure and immunoprecipitation followed by immunoblotting with scinderin and gelsolin antibodies. Among the tissues… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

1991
1991
2002
2002

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 16 publications
2
31
0
Order By: Relevance
“…These results do not rule out the possibility that other actin-binding proteins might have stronger affinities for actin. However, the present results as well as our earlier published experiments (Rodrfguez Del Castillo et al, 1990) demonstrate that both gelsolin and scinderin are equally retained by actin affinity columns.…”
Section: Ca 2+ and Ph Dependent Interactions Of Scinderin With Phosphsupporting
confidence: 82%
See 2 more Smart Citations
“…These results do not rule out the possibility that other actin-binding proteins might have stronger affinities for actin. However, the present results as well as our earlier published experiments (Rodrfguez Del Castillo et al, 1990) demonstrate that both gelsolin and scinderin are equally retained by actin affinity columns.…”
Section: Ca 2+ and Ph Dependent Interactions Of Scinderin With Phosphsupporting
confidence: 82%
“…Control experiments were carried out with (a) FITC-IgG alone and (b) scinderin antiserum previously adsorbed with scinderin. Scinderin antibodies were raised in rabbits against the purified bovine protein (Rodrfguez Del Castillo et al, 1990), scinderin antiserum 6 has been previously characterized (Tchakarov et ai., 1990;Vitaie et al, 1991).…”
Section: Immunofluorescence Microscopy Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, bovine adseverin had only been purified from adrenal and exocytotic cells (31). It was also immunologically detected in pituitary, brain, and kidney tissues after partial enrichment (25,28,37), again pointing at the low abundance of the protein. It is important to mention here that mouse adseverin is strongly upregulated in mast cells, which contain many granules and are known to be exocytotically active.…”
Section: Discussionmentioning
confidence: 98%
“…To study the distribution of scinderin and gelsolin in bovine adrenal chromaflin cells in culture, it was important to demonstrate the specificity of the polyclonal antisera to be used. Previous work from our laboratory demonstrated that scinderin and gelsolin antisera are specific for these proteins and that do not cross-react with any other chromaffin cell cytosolic protein (Bader et al, 1986;Rodriguez Del Castillo et al, 1990;Tchakarov et al, 1990). Cross-reactivity of both antisera with chromaffin cell cytoskeletal proteins was also investigated.…”
Section: R E S U L T S (A) Specificity Of Scinderin and Gelsolin Antimentioning
confidence: 95%